Peningkatan Etos Kerja Melalui Kedisiplinan Kepala Madrasah pada Guru MTsS Darul Falah Kabupaten Aceh Timur - Helmiah; Jamali (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2022)
The head of the madrasah (school) is someone who is given the task by his subordinates to lead a madrasa where the teaching and learning process is held in the madrasa. One of the things that can help teachers to be disciplined in teaching is to repeat the law. No. 14 of 2005 concerning the intent and duties of teachers in carrying out the teaching and learning process in schools. The purpose of this madrasah action research is to seek to improve the work ethic for MTsS Darul Falah teachers, East Aceh Regency through the discipline of the madrasah principal in the odd semester of the 2019/2020 school year, totaling 16 teachers. The research method used is the madrasah action research method which is carried out in two cycles the first four times consisting of 1) planning 2) implementation 3) observation and 4) reflection. In collecting this data, the researcher used observation, interviews and documentation. In the interview technique, the researcher wanted to dig up data about the causes and effects of not carrying out the work ethic on teaching attendance. The results showed that there was an increase in the work ethic of teachers through the discipline of the madrasa principal, namely in the first cycle the level of teacher work ethic from 16 teachers was only 63%. In the second cycle reached 88%. From the results of the study, it can be concluded that through discipline the head of the madrasa can improve the work ethic of teachers in teaching attendance so as to increase the creativity of students.